Toxic Masculinity through Ideological Violence in Antonio Campos’s The Devil All The Time Movie - Hizkia, Hendri Petrus; Rahmawati, Irma (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2025)
Toxic masculinity is a harmful behavior shaped by complex social and cultural pressures, as illustrated in The Devil All the Time (2020), which presents an environment full of trauma and violence that shapes male identity. This study examines the depiction of toxic masculinity and its impact, using Terry A. Kupers as the primary framework, supported by a film analysis approach. Using a qualitative descriptive method, the data were selected through dialogue techniques focused on the main character, Arvin Russell. The results identified three main characteristics of toxic masculinity depicted in Arvin’s character: emotional suppression, aggression, and violence. Additionally, it is also found that there is an impact of toxic masculinity, emotional isolation, and loneliness as a defense mechanism. Thus, this study concludes that toxic masculinity illustrated in the movie operates as a socially destructive force and has psychological impacts that are harmful to both individuals and society. Keywords: Toxic Masculinity, Ideological Violence, Emotional Suppression, The Devil All the Time, Film Analysis